The Phytoestrogen Quercetin Impairs Steroidogenesis and Angiogenesis in Swine Granulosa Cells In Vitro. (1st June 2009) - Santini, Sujen Eleonora; Basini, Giuseppina; Bussolati, Simona; Grasselli, Francesca
Abstract : Experimental evidence documents that nutritional phytoestrogens may interact with reproductive functions but the exact mechanism of action is still controversial. Since quercetin is one of the main flavonoids in livestock nutrition, we evaluated its possible effects on cultured swine granulosa cell proliferation, steroidogenesis, and redox status. Moreover, since angiogenesis is essential for follicle development, the effect of the flavonoid on Vascular Endothelial Growth Factor output by granulosa cells was also taken into account. Our data evidence that quercetin does not affect granulosa cell growth while it inhibits progesterone production and modifies estradiol17 β production in a dose-related manner. Additionally, the flavonoid interferes with the angiogenic process by inhibiting VEGF production as well as by altering redox status. Since steroidogenesis and angiogenesis are strictly involved in follicular development, these findings appear particularly relevant, pointing out a possible negative influence of quercetin on ovarian physiology. Therefore, the possible reproductive impact of the flavonoid should be carefully considered in animal nutrition.